Effect of heat treatment on the structural, morphology and electrochemical performance of perovskite Ba0.5Sr0.5Co0.8Fe0.2O3−δ-Sm0.2Ce0.8O1.9 carbonate protective coating for SOFC metallic interconnect - Tan, Kang Huai; Hamimah Abd.Rahman,; Hariati Mohd Taib, (Penerbit Universiti Kebangsaan Malaysia, 2020)
A composite perovskite Ba0.5Sr0.5Co0.8Fe0.2O3−δ-Sm0.2Ce0.8O1.9 carbonate (BSCF-SDCC) coating was investigated to enhance the performance of SUS 430 stainless steel as interconnect material for solid oxide fuel cells (SOFCs). BSCF-SDCC powder was successfully obtained by low-speed wet milling method from commercial BSCF, SDC, and binary carbonates. The developed BSCF-SDCC powder were heat-treated 600 °C for 90 min, and then characterized by X-ray diffraction (XRD) and field-emission scanning electron microscopy (FESEM) equipped with energy-dispersive spectroscopy (EDS). FESEM revealed better morphology of BSCF-SDCC powder with heat treatment. However, XRD analysis showed the destruction of BSCF phase in the BSCF-SDCC powder after heat treatment at 600 °C. Moreover, electrophoretic deposition (EPD) of BSCF-SDCC powder in an ethanol-added dispersing agent suspension was investigated under 10 volt 10 minutes by 10 g/l. The coated samples were then heat-treated at 600 °C. The coated samples were characterized by comparing between the samples with and without heat treatment based on XRD, SEM-EDS, and area specific resistance (ASR) analyses. XRD analysis indicated BSCF phases disappeared for the samples with heat treatment. The heat-treated sample performed better coating morphology and fewer pores. The samples underwent 500 hours of air oxidation at 600°C, and ASR was measured by DC 2-point method during in situ oxidation process. The coated sample with heat treatment at 600 °C exhibited excellent low area-specific resistance reading of below 0.1 Ωcm2, which is an essential requirement for interconnect materials. After 500 h of oxidation, the XRD patterns revealed stable phase and maintained good coating morphology.